The meaning of care for operating room nursing - Cléton Salbego; Carla da Silveira Dornelles; Patrícia Bitencourt Toscani Greco; Vania Marta Pradebon; Gabriela Fávero Alberti (Rev Rene)
Objective: to understand the meaning of care for nursing technicians who work in the Surgical Center of a general hospital in the western border of Rio Grande do Sul/Brazil. Methods: this is a qualitative research, with an exploratory and descriptive approach. The technique used for data collection was a semi-structured interview and notes from the field diary were available for support. The respondents were eight nursing technicians of the Surgical Center. Results: it can be emphasized that participants value psychological, social and affective aspects of patients and their families, also expressing a holistic view in regards to caring for themselves or others. Conclusion: in the referred unit, care is an activity involving multiple aspects, patients, families and staff. The meanings valued by professionals reveal detachment from technical aspects to value psychological, social and emotional aspects of care.